Analysis of the Solid Medical Waste Management System Personal Protective Equipment (PPE) at the Special Covid-19 Isolation Facility in Suryah Khairudin Regional General Hospital - Aini, Syarifah; Syarifuddin, Hutwan; Ilham, Ilham (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: The generation of solid medical waste Personal Protective Equipment (PPE) generated in special facilities for Covid19 isolation is increasing and is an infectious waste that poses a risk of transmitting Covid19 to the environment. The occupancy rate (BOR) in the Covid19 special isolation room at Suryah Khairudin Hospital in 2020 was 14.75% of 51 beds, with an average number of inpatients 13 people/month, the total amount of solid medical waste PPE produced reached 60.69 kg/month. Subjects and Method: This was a descriptive qualitative study. The study informants were waste management officers. The data were obtained from interviews and observation. The data were extracted and analyzed using SWOT analysis.Results: The PPE solid medical waste management system at the Suryah Khairudin Hospital as a special Covid19 facility in West Tanjung Jabung Regency is quite good in terms of sorting, transportation is carried out less than 24 hours after being collected, and processing is carried out using incinerator. This is in accordance with KMK No. HK 01.07/MENKES/537/2020. Meanwhile, what has not been fulfilled is the labeling of plastic bags containing PPE waste because the use of black bags is still found but it is not labeled